2017
DOI: 10.2175/106143015x14338845155066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biological and Mass Transfer Parameter Uncertainty on N2O Emission Estimates from WRRFs

Abstract: This research used the detailed activated sludge model (ASM) to investigate the effect of parameter uncertainty on nitrous oxide (N2O) emissions from biological wastewater treatment systems. Monte Carlo simulations accounted for uncertainty in the values of the microbial growth parameters and in the volumetric mass transfer coefficient for dissolved oxygen (kLaDO), and the results show that the detailed ASM predicted N2O emission of less than 4% (typically 1%) of the total influent Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In previous studies, several pathways for N 2 O production have been suggested, including denitrification by heterotrophic bacteria and AOB [15,43], biological and chemical reactions derived from hydroxylamine [45], the abiotic reaction of hydroxylamine with free nitrous acid [46,47] and a hybrid reaction between hydroxylamine and NO 2 − [26,48,49]. Particularly, N 2 O production from AOB denitrification has been reported to be the main pathway when DO concentration is approximately 1.0 mg L −1 [15,43,50], which is this study's condition.…”
Section: Mechanism Of N 2 O Productionmentioning
confidence: 99%
“…In previous studies, several pathways for N 2 O production have been suggested, including denitrification by heterotrophic bacteria and AOB [15,43], biological and chemical reactions derived from hydroxylamine [45], the abiotic reaction of hydroxylamine with free nitrous acid [46,47] and a hybrid reaction between hydroxylamine and NO 2 − [26,48,49]. Particularly, N 2 O production from AOB denitrification has been reported to be the main pathway when DO concentration is approximately 1.0 mg L −1 [15,43,50], which is this study's condition.…”
Section: Mechanism Of N 2 O Productionmentioning
confidence: 99%
“…Song et al (2017) investigated the parameter uncertainty on N2O emissions from biological treatment of wastewater using the activated sludge model. Results from the Monte Carlo simulations which accounted for the uncertainty in microbial growth parameters and DO mass transfer coefficient for (kLaDO) showed that the predicted N2O emission was < 4% (as compared to 1%) of the total influent ammonia load Zhou et al (2017).…”
mentioning
confidence: 99%